(untitled) (Agro Productividad, 2022)
L Objective: Stevia rebaudiana Bertoni is a crop that can meet the demand for natural sweeteners; however, this demand requires a sustainable production, as a result of the inclusion of its steviol glycosides or active ingredients in the food and pharmaceutical industries. Design/methodology/approach: Modern agriculture implies the integrated use of valid natural resources, such as the arbuscular mycorrhizal fungi (AMF). These microorganisms establish a symbiotic relationship with, at least, 80% of the plants, to which they provide multiple benefits. They can directly and indirectly improve crop productivity, through nutrient (particularly, phosphorus) translocation of the soil solution. Results: As a sustainable alternative for the production of S. rebaudiana, they improve its nutritional state, resulting in a higher biomass production and glycoside concentration —fundamental yield parameters. Additionally, they promote resistance to biotic and abiotic stress factors and improve soil quality. Limitations/implications: It is worth mentioning that this fungi-plant mutualism is approximately 400 million years-old; however, it has only aroused interest during the last few years. Findings/conclusions: Although arbuscular mycorrhizal fungi (AMF) are an exploitable resource, their communities are threatened by biotic factors —such as the interaction with other microorganisms— and abiotic factors —which involve bad agricultural practices.